ASCT2 inhibits HIV-1 infectivity by promoting the incorporation of a gp160/ASCT2 complex into virions - Luciana Morellatto Ruggieri; Eri Miyagi; Sandra Kao; Hideki Saito; Aymé Drake Figueredo; Haruki Kitamura; María I. Colombo; Klaus Strebel (mBio)
ABSTRACT Restriction factors are type I interferon (IFN)-inducible proteins that provide an early line of defense against HIV-1. Our current findings propose the amino acid transporter ASCT2 as a new host plasma membrane transporter that restricts the infectivity of HIV-1 viral particles. Our results show that ASCT2 is constitutively expressed in CD4+ T cells and macrophages, but its expression can be upregulated by the antiviral cytokine IFNα. We also found that ASCT2 is downmodulated from the cell surface of HIV-1-infected CD4+ T cells and macrophages. Our experiments suggest that ASCT2 interacts with the Env precursor gp160 in the endoplasmic reticulum (ER) and forms a complex of uncleaved gp160 and immature ASCT2. This complex can be incorporated into nascent viral particles and may lead to lower infectivity of progeny HIV-1. However, the restriction activity of ASCT2 against HIV-1 is counteracted by the accessory protein Vpu. We found that Vpu interacts with ASCT2 in the ER and prevents ASCT2 maturation through the N-glycosylation pathway, resulting in the downmodulation of ASCT2 from the plasma membrane. In summary, our results suggest that the amino acid transporter ASCT2 functions as an IFNα-inducible restriction factor against HIV-1 by promoting the incorporation of the complex formed by the inactive precursor of Env gp160 and immature ASCT2 into the viral particles, which is counteracted by the HIV-1 accessory protein Vpu.IMPORTANCEGlobally, there are about 39 million people living with HIV (PLWH). Antiretroviral treatment (ART) has transformed HIV infection into a chronic condition. However, effective ART does not cure HIV since the virus establishes long-lasting reservoirs that are resistant to currently available ART. Nowadays, the choice of the ART regimen depends on several factors, such as drug resistance, health conditions of PLWH, and possible side effects of medications. To address the complexity of the ART regimen, drug toxicities, and drug resistance, the research on novel formulations continues. Currently, new antiviral therapies are being developed that target important interactions between viral accessory proteins and host restriction factors, such as the interaction between Vpu and BST-2 and between Vif and APOBEC3. Therefore, our current findings about ASCT2 and Vpu not only provide novel insights about HIV-1 virus-host restriction factor interaction but also propose a novel and promising strategy to develop a new treatment against HIV.